Enhancement of Probiotic Viability and Antioxidant Activity in Yogurt Treated with Corn Silk Extract - Marya, Dina Tri; Nopitariyani, Arizki Tri; Maradon, Gusma Gama; Hanif, Muhammad (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Yogurt is a widely consumed fermented milk product known for its numerous health benefits, while corn silk, the pistil of corn, is a byproduct rich in bioactive compounds and antioxidants. This study assessed the antioxidant activity of yogurt fortified with corn silk extract. Yogurt was prepared by fermenting cow's milk with a yogurt starter culture. The antioxidant activity of the resulting yogurt was evaluated using the DPPH method. The results demonstrated that the yogurt enriched with corn silk exhibited a total lactic acid bacteria (LAB) count of 1.2 Ã— 108 cfu/mL, a pH of 4.4, a lactic acid content of 1.34%, and an antioxidant activity of 54%. In contrast, the control yogurt without corn silk had a LAB count of 1.9 Ã— 10â· cfu/mL, a pH of 4.5, a lactic acid content of 0.93%, and an antioxidant activity of 47%. Organoleptic evaluations revealed no significant differences in taste, aroma, texture, or overall acceptability between the two yogurt types. The addition of corn silk significantly increased the antioxidant activity, total microbial count, and lactic acid content of the yogurt. These findings suggest that corn silk extract can be a beneficial natural additive to enhance the antioxidant properties of yogurt, thereby improving its nutritional value.